Seed market segmentation increases maize production intensification in Africa - Yang, Jie; Xiong, Wei; Jaleta, Moti; Snapp, Sieglinde; Cairns, Jill; Rutsaert, Pieter; Zhang, Jiwang (CIMMYT, 2025)
The potential genetic gains of improved maize cultivars in Africa have not been fully realized, primarily due to limited access to seed information and market constraints. A well-designed seed market segmentation strategy can address these challenges by facilitating the dissimilation of improved cultivars and providing location-specific recommendations. Here we integrate location-specific data on climate, soil, terrain and agricultural inputs with a sampling crop modeling approach to assess cultivar suitability of maize with varying maturity requirements. Our findings reveal that the suitability of maize cultivars with different maturity has shifted over recent decades, influenced by both climate change and variations in planting time. Short-maturing maize cultivars dominant maize growing areas, although we observe cultivar migration in certain regions. By implementing a market segmentation strategy that optimizes cultivar maturity and sowing time, Africa has the potential to double its maize production on existing maize land, achieving sustainably intensification. However, realizing this potential requires complementary improvements in agricultural systems, including extension services, market infrastructure, and supportive policies. This study generates actionable insights to guide broader agricultural development efforts.